2020
DOI: 10.1159/000510446
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy Using Carboplatin plus Paclitaxel versus Cisplatin plus Fluorouracil for Esophageal or Gastroesophageal Junction Cancer

Abstract: <b><i>Background:</i></b> Trimodality therapy (TMT) with neoadjuvant chemoradiotherapy (nCRT) using concurrent carboplatin plus paclitaxel (CP) followed by surgery is the standard of care for locoregional esophageal or gastroesophageal junction (GEJ) cancers. Alternatively, nCRT with cisplatin plus fluorouracil (CF) can be used. Definitive chemoradiotherapy (dCRT) with CP or CF can be used if surgery is not planned. In the absence of comparative trials, we aimed to evaluate outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Currently, the 'National Comprehensive Cancer Network' guidelines give a category 1 recommendation for both regimens [19]. There have only been few retrospective studies, which could not consistently demonstrate a superiority for either regimen [8,[20][21][22]. Thus, this issue certainly remains of scientific interest [8].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the 'National Comprehensive Cancer Network' guidelines give a category 1 recommendation for both regimens [19]. There have only been few retrospective studies, which could not consistently demonstrate a superiority for either regimen [8,[20][21][22]. Thus, this issue certainly remains of scientific interest [8].…”
Section: Discussionmentioning
confidence: 99%
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria. Finally, a total of 31 articles involving 3432 participants were included [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The detailed retrieval process of this review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study by Jiang DM et al [ 73 ] compared carboplatin plus paclitaxel with cisplatin plus fluorouracil as chemotherapy regimens in patients with resectable tumors of the esophagus and GEJ that received neoadjuvant chemoradiotherapy. The study also included patients who did not proceed to surgical resection and received definitive chemoradiation.…”
Section: Treatmentmentioning
confidence: 99%
“…In patients who received surgery, no difference was observed between the two treatment groups. However, in the definitive chemoradiation subgroup, carboplatin-paclitaxel was associated with significantly worse 3-year OS (36% vs 63% P = 0.001 HR 3.1, 95%CI: 1.2-7.7) and DFS (0% vs 41%; P = 0.004; HR 3.6, 95%CI: 1.4-8.9)[ 73 ].…”
Section: Treatmentmentioning
confidence: 99%